The Role of Sharia Financial Innovation and Literacy for MSME Actors in Increasing Profitability - Diky Rahmansyah; Devita Veronika Saputri; Zathu Restie Utami; Yuanyuan Wang (Sharia Oikonomia Law Journal, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role, especially in expanding employment, increasing community income so that they can become drivers of development and economic growth. The slow development of MSMEs is caused by low levels of financial literacy and lack of innovation, causing the welfare of MSMEs or the community to decline. The research method used is a literature review approach to analyze various information and data that are quantitative and qualitative in nature, especially in articles published in national journals. The results showed that the development of innovation and Islamic financial literacy in Indonesia is characterized by three main things, namely; (1) The growth of the Islamic Financial Market along with the growth of Islamic financial institutions in the midst of society, (2) The growing Islamic financial literacy achieved by increasing the knowledge, skills and confidence of the community so that they are able to carry out financial management wisely and efficiently, (3) The development of Islamic financial fintech.